Educational justice. Issue 12 (2nd November 2020) - Culp, Julian
Abstract: Philosophical conceptions of educational justice are centered at the intersection of political philosophy and philosophy of education. They justify moral‐political rights to education and sometimes also determine who is responsible for their realization through which kinds of pedagogical practices or systemic educational reform. This article concentrates on contemporary conceptions of educational justice in primary and secondary education and highlights central practical implications that the various conceptions of educational justice have under non‐ideal circumstances. Section 2 explains the conceptions of fair and luck‐egalitarian equal educational opportunity, Section 3 the conception of educational priority for the least‐advantaged students, and Section 4 the conception of democratically adequate education . Finally, Section 5 presents a philosophical conception of global justice in school education . Section 6 concludes.